Analisis Perilaku Kerja Karyawan Pada PT Bumi Nyiur Swalayan (BNS) Pusat - Arum Dani; Husnah; Risnawati; Mohammad Ega Nugraha (Pusat Riset dan Inovasi Nasional, 2023)
Employee work behavior in the form of actions or attitudes or assumptions about their own work. Every company should know how the work behavior of its employees. Employee work behavior leads to the achievement of company goals, and will have an impact on company performance. The purpose of this study was to analyze the work behavior of employees at the main branch of PT. Bumi Nyiur Swalayan (BNS) Palu. Sources of data in this study come from primary data, through surveys, observations, and interviews. The target of this research which is the research population is all employees of PT. Bumi Nyiur Swalayan (BNS) Palu as many as 69 people. The results of the research show the behavior of employees at PT. Bumi Nyiur Swalayan (BNS) Palu, has motivation, can show work productivity, responsible and work hard.